Drug name searcher : medication term recognition system design and implementation - Ma, Yuqian (Nanyang Technological University, 2020)
This is the FYP report on the Final Year Project “Drug Name Searcher”, which aims to detect and recognize medication name entities in unstructured medical texts. Drug Name Recognition (DNR) has been an important and fundamental task for many medication systems to maximize the usage of resources and information in medical texts. Many effort and advanced researches have been done in this area. Here we present the current research and experiments that have been done on this topic and the work that can be broadened in the future.